Retrospective study on Porcine circovirus-2 by nested pcr and real time pcr in archived tissues from 1978 in Brazil - Silva,Fernanda Miquelitto Figueira da (2011)
Porcine circovirus-2 (PCV-2) infection is currently considered an important disease of swine. The pathogenic agent was first described in Brazil in 2000. This study detected the PCV-2 DNA in four Brazilian pig tissues collected between 1978 and 1979. This observation is the oldest description of this virus in Brazil.